2021
DOI: 10.3390/genes12030415
|View full text |Cite
|
Sign up to set email alerts
|

Production of Membrane Vesicles in Listeria monocytogenes Cultured with or without Sub-Inhibitory Concentrations of Antibiotics and Their Innate Immune Responses In Vitro

Abstract: Listeriosis is a food-borne illness caused by Listeria monocytogenes. Ampicillin (AMP) alone or in combination with gentamicin (GEN) is the first-line treatment option. Membrane vesicle (MV) production in L. monocytogenes under antibiotic stress conditions and pathologic roles of these MVs in hosts have not been reported yet. Thus, the aim of this study was to investigate the production of MVs in L. monocytogenes cultured with sub-minimum inhibitory concentrations (MICs) of AMP, GEN, or trimethoprim/sulfametho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Interestingly, we found that the averaged diameter of 103 + -EVs (130 nm) is slightly bigger than 103 − -EVs (105 nm) ( Figure 1 ). The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that the averaged diameter of 103 + -EVs (130 nm) is slightly bigger than 103 − -EVs (105 nm) ( Figure 1 ). The size of EVs in Gram-positive bacterial varies between different bacterial strains [ 34 , 35 , 36 , 37 ], throughout various stages of bacterial growth [ 38 ], and environmental conditions [ 27 , 39 , 40 ]. As the reports that the size distribution of EVs of the invasive Streptococcus pyogenes strains SSI-1 were 1.31 times bigger than the non-invasive Streptococcus pyogenes strains JRS4 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many aspects of inter-kingdom communication by small regulatory RNAs in vesicles are either poorly understood or unknown and require additional study. For example, the effect of growth conditions, temperature, and antibiotics on vesicle secretion and small regulatory RNA content of OMVs and BEVs are not well understood [ 22 , 44 , 51 , 76 , 77 ]. A few studies have shown that small regulatory RNAs are differentially packaged in vesicles and that the sRNA content of BEVs and OMVs is dependent on growth conditions and antibiotics [ 22 , 44 , 51 , 76 ].…”
Section: Future Prospectsmentioning
confidence: 99%